2006
DOI: 10.1073/pnas.0509683103
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint structure reveals the unique origin of an interspecific chromosomal inversion ( 2La ) in the Anopheles gambiae complex

Abstract: Paracentric chromosomal inversions are major architects of organismal evolution and have been associated with adaptations relevant to malaria transmission in anopheline mosquitoes. The processes responsible for their origin and maintenance, still poorly understood, can be illuminated by analysis of inversion breakpoint sequences. Here, we report the breakpoint structure of chromosomal inversion 2La from the principal malaria vector Anopheles gambiae and its relatives in the A. gambiae complex. The distal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
136
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 21 publications
13
136
0
Order By: Relevance
“…The major malaria resistance locus, PRI, has 56 conserved syntenic blocks with a median length of ∼45 kb. The PRI was detected previously in mosquitoes with a chromosomal inversion between 20,528,089 and 42,165,532 bp (4,9,19). However, our map is based on the pink-eye standard (PEST) strain, which lacks this inversion, being used as the reference genome.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The major malaria resistance locus, PRI, has 56 conserved syntenic blocks with a median length of ∼45 kb. The PRI was detected previously in mosquitoes with a chromosomal inversion between 20,528,089 and 42,165,532 bp (4,9,19). However, our map is based on the pink-eye standard (PEST) strain, which lacks this inversion, being used as the reference genome.…”
Section: Resultsmentioning
confidence: 97%
“…This strategy differs from approaches that determine candidate genes on the basis of the differentially expressed genes under parasite challenge. Seventy known genes were used to label genomic blocks on the expression The PRI was detected originally in mosquitoes with a chromosomal inversion that is absent in the reference genome strain (4,9,19). This results in two noncontiguous PRI domains in the map shown here.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, A. gambiae expanded beyond its ancestral range in the rainforests of central Africa into arid environments of sub-Saharan Africa 3000-11 000 years ago. Adaptation to the arid environment is associated with a chromosomal inversion, 2La, which is ancestral to the arid-adapted species A. arabeinsis [89]. Critically, genetic analyses have revealed that introgression from A. arabeinsis into A. gambiae resulted in the transfer of the 2La inversion [63,65,66].…”
Section: (A) Introgression Of Adaptive Allelesmentioning
confidence: 99%
“…The gene region was inverted as compared with species of the Sophophora subgenus, and the hsp26 gene is duplicated in the virilis and the repleta groups. Some inversions arise by simple cut and paste events, others arise by more complicated events which may result in duplication of coding sequences at the break points (Matzkin et al 2005;Sharakhov et al 2006). Since D. buzzatii phsp26 and D. buzzatii hsp26 are located at the borders of the inversion, it seems likely that the hsp26 duplication originated together with the inversion event, but there could be several explanations of the origin of the inversion/duplication events.…”
Section: Discussionmentioning
confidence: 99%